Comprehensive Analysis of the Transcriptome-Wide m6A Methylation Modification Difference in Liver Fibrosis Mice by High-Throughput m6A Sequencing - Fan, Chang; Ma, Yanzhen; Chen, Sen; Zhou, Qiumei; Jiang, Hui; Zhang, Jiafu; Wu, Furong (Frontiers in Cell and Developmental Biology, 2021)
N6-Methyladenosine (m6A), a unique and common mRNA modification method in eukaryotes, is involved in the occurrence and development of many diseases. Liver fibrosis (LF) is a common response to chronic liver injury and may lead to cirrhosis and even liver cancer. However, the involvement of m6A methylation in the development of LF is still unknown. In this study, we performed a systematic evaluation of hepatic genome-wide m6A modification and mRNA expression by m6A-seq and RNA-seq using LF mice. There were 3315 genes with significant differential m6A levels, of which 2498 were hypermethylated and 817 hypomethylated. GO and KEGG analyses illustrated that differentially expressed m6A genes were closely correlated with processes such as the endoplasmic reticulum stress response, PPAR signaling pathway and TGF-β signaling pathway. Moreover, a total of 90 genes had both a significant change in the m6A level and mRNA expression shown by joint analysis of m6A-seq and RNA-seq. Hence, the critical elements of m6A modification, including methyltransferase WTAP, demethylases ALKBH5 and binding proteins YTHDF1 were confirmed by RT-qPCR and Western blot. In an additional cell experiment, we also observed that the decreased expression of WTAP induced the development of LF as a result of promoting HSC activation. Therefore, this study revealed unique differential m6A methylation patterns in LF mice and suggested that m6A methylation was associated with the occurrence and course of LF to some extent.